Pengaruh Pelatihan dan Pendidikan terhadap Pengembangan Karir Karyawan pada Satuan Kerja Non Vertikal Tertentu (SNVT) Pembangunan Jalan dan Jembatan Provinsi NTB - Irwan Cahyadi; Isra Dewi Kuntary Ibrahim; Rini Anggriani; Raden Bagus Faizal Irany Sidharta (Target : Jurnal Manajemen Bisnis, 2021)
The purpose of this study was to determine the significance of the effect of components of education and training programs such as materials, teaching staff, methods, time, location and facilities on the career development of employees in Certain Non-Vertical Work Units (SNVT) for Road and Bridge Construction of NTB Province, both partially and simultaneously. The type of research used is descriptive research and uses a sample survey method in collecting data. The data collection tool used is a questionnaire, in which each variable being studied is made up of measurement indicators arranged in the relevant questionnaire. The analytical tool used in accordance with the objectives of the researcher is multiple linear regression analysis, which is then continued with the F test and t test at 5% alpha. Based on the results of the analysis carried out, it is known that the components of the education and training program such as materials, teaching staff, methods, time, location and facilities have a significant influence on the career development of employees in Certain Non-Vertical Work Units (SNVT) for Road and Bridge Construction in the Province of NTB. simultaneously or partially. The significance criteria are known based on the F test and t test that have been carried out, where F count and t count have a higher value than F table and t table.